2022
DOI: 10.1186/s13244-022-01188-6
|View full text |Cite
|
Sign up to set email alerts
|

Signal enhancement ratio of CE-MRI: a potential biomarker of survival after hepatic arterial infusion chemotherapy in biliary tract cancers

Abstract: Background The association of contrast-enhanced MRI (CE-MRI) and the overall survival (OS) of biliary tract cancers (BTC) is ambiguous. Thus, the aim of this study is to evaluate the value of signal enhancement ratio (SER) and its early change in CE-MRI as biomarkers of survival after hepatic arterial infusion chemotherapy (HAIC) in BTC. Results One hundred and two BTC patients treated via HAIC with 3cir-OFF regimen between January 2011 and June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Another report showed that pembrolizumab monotherapy in BTC patients with PD-L1 expression in 1% or more of tumor cells or with tumor-infiltrating lymphocytes achieved responses in 4 out of 24 (17%) patients ( 19 ). Hepatic artery infusion chemotherapy (HAIC) in combination with immunotherapy also has high anti-tumor activity ( 20 – 22 ). One retrospective study pooled over 100 BTC patients treated via HAIC with the 3cir-OFF regimen, which is comprised of oxaliplatin, 5-fluorouracil, and folinic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report showed that pembrolizumab monotherapy in BTC patients with PD-L1 expression in 1% or more of tumor cells or with tumor-infiltrating lymphocytes achieved responses in 4 out of 24 (17%) patients ( 19 ). Hepatic artery infusion chemotherapy (HAIC) in combination with immunotherapy also has high anti-tumor activity ( 20 – 22 ). One retrospective study pooled over 100 BTC patients treated via HAIC with the 3cir-OFF regimen, which is comprised of oxaliplatin, 5-fluorouracil, and folinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study pooled over 100 BTC patients treated via HAIC with the 3cir-OFF regimen, which is comprised of oxaliplatin, 5-fluorouracil, and folinic acid. The median PFS and OS of patients receiving this regimen were 9.8 months and 14.2 months, respectively ( 22 ). A study from China showed that tislelizumab was also observed to have anti-tumor activities in other solid tumors with an ORR ≥15% including nasopharyngeal carcinoma (43%), MSI-H/deficient mismatch repair (dMMR) solid tumors (19%), non-small cell lung cancer (18%), gastric cancer (17%), hepatocellular carcinoma (17%), and melanoma (15%) ( 23 ).…”
Section: Discussionmentioning
confidence: 99%